Litterfall production of the natural - recovered secondary forest at the Melinh station for biodiversity, Vinhphuc province - Tan, Le Dong; Chung, Do Hoang (Academia Journal of Biology, 2014)
The litterfall is an important link of the chain to transport organic materials and mineral substances from the vegetation into the soil in ecosystems. There are many factors controlling the litterfall production: site conditions, fertility of the soil, growth season, composition and age of the plant.… The study of the litterfall production takes part to clear the matter cycle and the nutritive cycle in ecosystems. It also defines the ability to return nutritive elements of the vegetation to the soil. Five permanent plots (with signs ML1, ML2, ML3, ML4 and ML5) were choosed to collect litterfall samples in the secondary forest from age of 10 years to age of 25 years at the Melinh station for Biodiversity, Vinhphuc province. The dominant species in these plots were mainly defoliated species such as: Toxicodendron succedanea (L.) Mold., Canarium parvum Leenh., Cratoxylum polyanthum (in ML1); Liquidambar formosana Hance, Toxicodendron succedanea (L.) Mold., Canarium parvum Leenh. (in ML2); Styrax tonkinensis (Pierre) Craib. ex Hartwiss, Toxicodendron succedanea (L.) Mold. (in ML3); Bischofia javanica Blume (in ML5). The litterfall samples were collected monthly in 3 random distributed traps with dimension of 1 m2 (1 m ´ 1 m) in two years, from 2004 to 2005. The data showed that the litterfall production of the secondary forests was 8.24 T/ha-15.69 T/ha per year; the average was 68.68-130.75 g/m2 per month. The rate of leaves was from 71.04% to 85.89% and the rate of branchs from 1.41% to 4.03% in total of the litterfall production in year. There were differences in total and branch litterfall production between the plots. They were in order ML1 < ML2 < ML3 < ML4 < ML5. The distribution of the litterfall production in months in 5 plots was also presented in this report. The data showed that the plot ML5 had one peak of litterfall in August and the other plots had two peaks: the first peak was from July to September and the second one was from November to February. The litterfall production depended on the composition and the defoliated particularity of species in the communities.